Investigation of Selected Biomotor Ability And Technical Skills in 10-11 Years Old Badminton Athletes - Hakan Ekin; Faruk Akçınar (Selcuk University, 2020)
This study was conducted to investigate the selected biomotor ability and technical skills of 10-11 year old badminton athletes and to determine the relationship between biomotor characteristics and technical skills. The sample of the study consists of athletes who are actively playing badminton in the 10-11 age groups in Kayseri and Batman provinces and have a badminton history of at least 1 year. For this study, French amp; Stalter badminton test, Lockhart amp; McPherson badminton test, agility t test, reaction test, vertical jump test and hand grip strength measurement were applied. Pearson correlation, independent-samples t test and one-way anova test were used for statistical analysis. Significance level was accepted as α = 0.05. While there was a negative correlation between technical tests and agility t test results; there was a positive relationship between anaerobic power. No significant correlation was found between vertical jump, hand grip left hand and handgrip right hand and technical tests. While there was a negative correlation between French amp; Stalter technical test and reaction visual right hand; There was no significant relationship between McPherson amp; Lockhart technical test. French amp; Stalter and McPherson amp; Lockhart technical tests showed no significant relationship between reaction visual left hand, reaction auditory right hand and left hand. As a result of 10-11-year-old badminton athletes selected biomotor ability and the technical skills investigated in this study, while a significant relationship was found between technical tests and agility and anaerobic power, and French amp; Stalter technique test and reaction visual right hand; vertical jump, hand grip left hand, handgrip right hand visual reaction left hand, auditory reaction right hand and auditory reaction left hand, no significant correlation was found between technical tests.